2015
DOI: 10.3390/e18010017
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Lattice Boltzmann Simulation of Liquid Water Transport in Porous Layer of PEMFC

Abstract: A three-dimensional two-phase lattice Boltzmann model (LBM) is implemented and validated for qualitative study of the fundamental phenomena of liquid water transport in the porous layer of a proton exchange membrane fuel cell (PEMFC). In the present study, the three-dimensional microstructures of a porous layer are numerically reconstructed by a random generation method. The LBM simulations focus on the effects of the porous layer porosity and boundary liquid saturation on liquid water transport in porous mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The LBM consists of two main steps: collision and streaming. The evolution of the distribution function f a ( x , t ) is as follows: fa(),boldx+eanormalΔtt+Δtfa(),xt=ΔtTr()fa(),xtfaeq(),xt …”
Section: Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The LBM consists of two main steps: collision and streaming. The evolution of the distribution function f a ( x , t ) is as follows: fa(),boldx+eanormalΔtt+Δtfa(),xt=ΔtTr()fa(),xtfaeq(),xt …”
Section: Methodologiesmentioning
confidence: 99%
“… T r represents the relaxation time required to achieve the equilibrium distribution faeq. A collision operator denotes the collision as a relaxation of the density distribution function toward the Maxwell‐Boltzmann equilibrium distribution function . In the D3Q19 scheme, the collision operator faeq is the Maxwellian distribution function, which is expressed as faeq(),xt=ωaρ(),xt[]1+eaueqcs2+eaueq2cs4()boldueq22cs2 where ω a is the weighting associated with the velocity e a , and it is defined for 19 components as follows: ωa={1/34ema=01/183.36ema=1,0.5em2,,0.5em61/363.36ema=7,0.5em8,,0.5em18 where c s is the lattice sound velocity, which is equal to 1/3 for the D3Q19 model.…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct numerical simulation method, computationally demanding but solving all the turbulent scales, has been recently used together with VOF to capture the detailed turbulent two‐phase flow in channel . To more accurately capture the droplet dynamics at pore scale, lattice boltzmann method (LBM) is effective, thus it is employed for multiphase flow simulation in the nanostructured CL . Based on the single relaxation time Bhatnagar‐Gross‐Krook evolution and Shan‐Chan model, the LBM model could capture the dynamics of water transport in the porous electrodes of PEMFC.…”
mentioning
confidence: 99%
“…6,7 To more accurately capture the droplet dynamics at pore scale, lattice boltzmann method (LBM) is effective, thus it is employed for multiphase flow simulation in the nanostructured CL. 8 Based on the single relaxation time Bhatnagar-Gross-Krook evolution and Shan-Chan model, the LBM model could capture the dynamics of water transport in the porous electrodes of PEMFC. It is found that the liquid water transport is strongly affected by the microstructure of the porous layer and the liquid water tends to flow through the large pores.…”
mentioning
confidence: 99%